The Schizophrenia in The Main Character of A Beautiful Mind movie Directed by Ron Howard. - Sri Arfani (LPPM Universitas Bina Sarana Informatika, 2018)
ABSTRACTIn literary works character and characterization are important elements because they built the story. Character is a person represented in a movie, story or other narrative work. In the movie, the character can be used as a field to be analyzed, one of which is psychology. Psychology that discussed in this paper in term of psychological illness that is schizophrenia. The objective of this analyze is to know the schizophrenia that experienced by main character, John Nash that taken from A Beautiful Mind movie. The Analysesare kinds of schizophrenia, the struggles of Nash, and the moral value that we can get from this movie. There are 3 Kinds of schizophrenia that showed in this movie. First, paranoid schizophrenia. The symptoms of paranoid are hallucinations and delusions. Second, disorganized schizophrenia. There are symptoms that experienced by disorganized schizophrenia: disorganized speech and disorganized behavior. Third, undifferentiated schizophrenia. The symptoms is seeming lack of interest in the world: social withdrawal. As the result of schizophrenia that experienced by John Nash, he experience of better alteration. At the end, Nash win the Nobel Prize. Although his hallucination friends never gone, but he never think about it.Keywords: Character, Psychological Disorder, Schizophrenia, A Beautiful Mind Movie